Collective oscillations in a bubble column - Yoon, S; Park, K; Crum, L; Nicholas, M; Roy, R; Prosperetti, A; Lu, N (Kluwer Academic Publishers, 1993)
A physical mechanism that could account for some of the sound generation in the ocean is the production of bubble clouds by ocean surface agitation. From our laboratory study of the sound generated by bubble clouds it is demonstrated that the individual bubbles can engage in collective oscillations that portray a gross feature of the cloud itself. The agreement between the measured collective mode frequencies and the theoretical predictions give evidence that a major source of ocean ambient noise in the few hundred hertz region may be that associated with the collective oscillations of bubble clouds.